Disqualifying the High Court. - Virelli, Louis (University Press of Kansas, 2016)
Judges recuse themselves when the outcome of a case might affect their personal interest or if there is reasonable belief that they would be biased because they have already taken a position on a case. For example, in a recent decision the Supreme Court decided that a member of the West Virginia Supreme Court should have recused himself from a decision involving a company that had made a substantial contribution to his election campaign. Who sets the standards for recusal and what standards are appropriate? Can Congress regulate the recusal rules for a co-equal branch, particularly the Supreme Court? What considerations go into making decisions about recusal? In this book Lou Virelli argues that Congress cannot set standards that must be followed by the Supreme Court because of separation of powers. The issue is less clear for the lower federal courts. In considering what standards should apply the courts must balance the due process claims of litigants with the right of judges to exercise their free speech rights. This book explores the history and grounds of judicial recusal by focusing mostly on the federal courts. Beyond the important question of recusal itself, the book explores the constitutional problems associated with separation of powers--